Juvenile Hyaline Fibromatosis is an Autosomal Recessive Genetic Disease. Four Cases Report - Manuel, Aparicio-Rodríguez J; MdL, Hurtado-Hernández; Margarita, Barrientos-Pérez; Sergio, Chatelain-Mercado (Journal of Asian Scientific Research, 2013)
Juvenile hyaline fibromatosis (JHF) is considered a non frequent genetic, autosomic recessive; characterized by connective tissue disorder characterized by multiple subcutaneous nodules, gingival hypertrophy, osteolytic lesions, and joint deformities (contractures). As one of the main clinical symptoms, are multiple subcutaneous nodules, articular contractures, and gingival hypertrophy after 6 months of life. After one year old the subcutaneous nodules appears more frequently among teenagers a great variety of deformations are observed with movement limitations. 70 cases with JHC approximately are reported in the literature.